Practising Cultural Inclusivity During the Pandemic: A Case Study of an Online Composition Course in Canada - Xia, Jing (MUSICultures, 2023)
The PhoeNX Ensemble-Memorial University composition course offers a case study of university-level pedagogical, intercultural music-making and its potential to engage the question of how music education can help to address existing racial and cultural tensions in society. During the course, racial and cultural concerns surfaced when participants negotiated their individual positionalities. An analysis of the multifaceted interactions demonstrates how this composition course exemplifies a meaningful and valuable path toward inclusive and anti-racist pedagogy in the Canadian classroom. Such approaches can address cultural misunderstanding and social injustice in the university context.